Novel PEGylated derivatives of α-tocopherol for nanocarrier formulations; synthesis, characterization and in vitro cytotoxicity against MCF-7 breast cancer cells. (15th May 2021) - Savadkouhi, Niloofar; Mazarei, Zeinab; Esmaeelzadeh, Maryam; Salehi, Peyman; Rafati, Hasan
Graphical abstract: Abstract: Despite numerous beneficial therapeutic effects namely antioxidant and anti-inflammatory activity, Vitamin E has limited clinical applications due to its low water solubility. Throughout the present work, α-tocopherol's new PEGylated derivatives alongside with polyethylene glycol 300 (α- 1 TPGT 300 ), 400 (α-TPGT 400 ), and 1000 (α-TPGT 1000 ) were synthesized. A 1, 2, 3-triazole ring was utilized as a linker for the attachment of alpha tocopherol to the PEGs through a click reaction. The purified derivatives were characterized by the means of 1 H NMR, 13 C NMR, mass spectroscopy, UV–vis and FT-IR methods. Synthesized derivatives' capacity to produce self-assembly nanoparticles was evaluated employing the critical micelle concentration (CMC) values. The stability of the micelles was studied by size analysis. In vitro cytotoxicity of the products was investigated using MTT assay against MCF-7 breast cancer cells. The IC50 value for TPGT 1000 after 24 h treatment was 15.0 ± 1.8 µM, whereas no significant cytotoxicity effect was observed following the treatment of MCF-7 cells by TPGT 300, 400 . The present study showed that polymeric micelle TPGT 1000 possessed better physicochemical and biological properties including relatively lower CMC value, higher stability in FBS environment in addition to higher cytotoxicity against MCF-7 breast cancer cells compared to the lower molecular weight PEGylated derivatives. These results confirmed that increasing PEG chain length left a positive effect on the polymeric micelle properties and also improved the cytotoxicity effect of new PEGylated vitamin E derivatives.